2017
DOI: 10.1371/journal.pone.0183502
|View full text |Cite|
|
Sign up to set email alerts
|

Different cadences and resistances in sub-maximal synchronous handcycling in able-bodied men: Effects on efficiency and force application

Abstract: BackgroundWith the introduction of an add-on handcycle, a crank system that can be placed in front of a wheelchair, handcycling was made widely available for daily life. With it, people go into town more easily, e.g. to do groceries; meet up with friends, etc. They have more independency and can be socially active. Our aim is to explore some settings of the handcycle, so that it can be optimally used as a transportation device. Therefore, the effects of cadence and added resistance on gross mechanical efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Similarly, higher cadences may be related to greater instability, which would imply higher needs of muscle activation for postural control and would ultimately lead to higher energy consumption, and therefore, worse efficiency [ 45 ]. When compared to studies in other sports, our findings were in agreement with those of Neilsen et al [ 46 ] and Jacobs et al [ 20 ] in cycling, Gonzalez-Aramendi [ 24 ] in traditional rowing, and Kraaijenbrink et al [ 25 ] in hand cycling, as all of them found that lower cadences were related to better efficiency and economy values. In contrast, Lucia et al [ 21 ] and Mora-Rodriguez and Aguado-Jimenez [ 47 ] in cycling, or Goosey et al [ 26 ] in hand cycling reported that higher cadences were more efficient and economical.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, higher cadences may be related to greater instability, which would imply higher needs of muscle activation for postural control and would ultimately lead to higher energy consumption, and therefore, worse efficiency [ 45 ]. When compared to studies in other sports, our findings were in agreement with those of Neilsen et al [ 46 ] and Jacobs et al [ 20 ] in cycling, Gonzalez-Aramendi [ 24 ] in traditional rowing, and Kraaijenbrink et al [ 25 ] in hand cycling, as all of them found that lower cadences were related to better efficiency and economy values. In contrast, Lucia et al [ 21 ] and Mora-Rodriguez and Aguado-Jimenez [ 47 ] in cycling, or Goosey et al [ 26 ] in hand cycling reported that higher cadences were more efficient and economical.…”
Section: Discussionsupporting
confidence: 92%
“…Considering that this sport takes place in natural environments, with changing wind and waves, the paddling cadence during open sea SUP races may not be constant. Several studies in other sports have suggested that some cadences are more efficient than others [ 6 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In the case of cyclists and triathletes, Jacobs et al [ 20 ] showed how lower cadences were more economical in trained subjects, while de Lucia et al [ 21 ] obtained opposite results with world-class cyclists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-and post-test consisted of level handcycling without additional resistance (~15 W) at 60 rpm [9,17,29]. In the three practice sessions, resistance (+ 0 W, + 10 W, + 20 W) and cadence (52, 60, 70 rpm) were varied as part of a bigger research project [30,31]. To ensure a physiological steady state, only the last minute of the selected four-minute blocks were analyzed with Matlab (MATLAB 2018b, Math-Works Inc., Natick, Massachusetts, USA).…”
Section: Set-up and Protocolmentioning
confidence: 99%
“…Whole-body measures of exercise physiology in upper body exercise (e.g., (5,6)) are limited in their detail in both healthy and clinical populations. Intramuscular metabolic processes during dynamic exercise require different, more local and preferably non-invasive measures to more accurately monitor and understand the energetic processes of exercise, adaptation, practice or training in healthy as well as clinical and pathologic populations (7).…”
Section: Introductionmentioning
confidence: 99%